Survival in ventricular fibrillation with emphasis on the number of defibrillations in relation to other factors at resuscitation. (April 2017) - Holmén, Johan; Hollenberg, Jacob; Claesson, Andreas; Herrera, Maria Jiménez; Azeli, Youcef; Herlitz, Johan; Axelsson, Christer
Abstract: Introduction: Mortality after out of hospital cardiac arrest (OHCA) is high and a shockable rhythm is a key predictor of survival. A concomitant need for repeated shocks appears to be associated with less favorable outcome. Aim: To, among patients found in ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT) describe: (a) factors associated with 30-day survival with emphasis on the number of defibrillatory shocks delivered; (b) the distribution of and the characteristics of patients in relation to the number of defibrillatory shocks that were delivered. Methods: Patients who were reported to The Swedish Register for Cardiopulmonary Resuscitation (SRCR) between January 1 1990 and December 31 2015 and who were found in VF/pVT took part in the survey. Results: In all there were 19, 519 patients found in VF/pVT. The 30-day survival decreased with an increasing number of shocks among all patients regardless of witnessed status and regardless of time period in the survey. In a multivariate analysis there were 12 factors that were associated with the chance of 30-day survival one of which was the number of shocks that was delivered. For each shock that was added the chance of survival decreased. Factors associated with an increased 30-day survival included CPR before arrival of EMS, female sex, cardiac etiology and year of OHCA (increasing survival over years). Factors associated with a decreased chance of 30-day survival included: increasing age, OHCA at home, the use of adrenaline and intubation and an increased delay to CPR, defibrillation and EMS arrival. Conclusion: Among patients found in VF/pVT, 7.5% required more than 10 shocks. For each shock that was added the chance of 30-day survival decreased. There was an increase in 30-day survival over time regardless of the number of shocks. On top of the number of defibrillations, eleven further factors were associated with 30-day survival.